Comprehensive investigation of the electronic excitation of W(CO)6 by photoabsorption and theoretical analysis in the energy region from 3.9 to 10.8 eV - Mónica Mendes; Khrystyna Regeta; Filipe Ferreira da Silva; Nykola C. Jones; Søren Vrønning Hoffmann; Gustavo García; Chantal Daniel; Paulo Limão-Vieira (Beilstein Journal of Nanotechnology, 2017)
High-resolution vacuum ultraviolet photoabsorption measurements in the wavelength range of 115–320 nm (10.8–3.9 eV) have been performed together with comprehensive relativistic time-dependent density functional calculations (TDDFT) on the low-lying excited sates of tungsten hexacarbonyl, W(CO)6. The higher resolution obtained reveals previously unresolved spectral features of W(CO)6. The spectrum shows two higher-energy bands (in the energy ranges of 7.22–8.12 eV and 8.15–9.05 eV), one of them with clear vibrational structure, and a few lower-energy shoulders in addition to a couple of lower-energy metal-to-ligand charge-transfer (MLCT) bands reported in the literature before. Absolute photoabsorption cross sections are reported and, where possible, compared to previously published results. On the basis of this combined experimental/theoretical study the absorption spectrum of the complex has been totally re-assigned between 3.9 and 10.8 eV under the light of spin–orbit coupling (SOC) effects. The present comprehensive knowledge of the nature of the electronically excited states may be of relevance to estimate neutral dissociation cross sections of W(CO)6, a precursor molecule in focused electron beam induced deposition (FEBID) processes, from electron scattering measurements.